The Relationship between Basic Immunization Services and Mother Baby Satisfaction at the Puskesmas Kwala Bekala Medan Johor in 2022 - Parningotan Simanjuntak; Nopalina Damanik (Science Midwifery, 2022)
Immunization is an effort to gain immunity against a disease by inserting germs or germ products that have been weakened or killed into the body to fight germs or germs that attack the body. This study aims to determine the relationship between basic immunization services and maternal infant satisfaction at the kwala bekala health center in 2022. This type of research is an analytical survey research with a cross sectional method approach. The population is all mothers of children under five at Kwala Bekala Health Center, totaling 171 people. The number of samples used is 64 people obtained by using simple random sampling that is taking a simple random sample. Data analysis technique using chi square. The results obtained are the appropriate tangibles variable as many as 51 respondents (92.75) who stated that they were satisfied higher than those who did not state that they were not satisfied as many as 4 respondents (44.4%) where the p value = 0.000. The appropriate reliability variable was 50 respondents (94.3%) who stated that they were satisfied higher than the unsatisfied one. 5 respondents (45.5%) stated that the p value = 0.000. The appropriate responsiveness variable was 51 respondents (92, 75) who stated that they were satisfied were higher than those who did not agree that they were not satisfied as many as 4 respondents (44.4%) where the p value = 0.000. Assurance variables that fit as many as 47 respondents (97.9) who stated that they were satisfied were higher than those who did not stated that they were not satisfied as many as 8 respondents (50%) where p value = 0.000. The appropriate Empathy variable was 45 respondents (93.8) who stated that they were satisfied higher than those who were not satisfied. 10 respondents (62.5%) stated that the p value = 0.002. That there was a relationship between Basic Immunization Services and Mother Baby Satisfaction.